Hypertriglyceridemia: An indicator of poor prognosis in acute pancreatitis – A hospital based study - Mushtaq, Mosin; Wani, Abid H; Sadiq, Faud; Mushtaq, Mudasir; Tabassum, Sameena; Mudasir, Taiba (Asian Journal of Medical Sciences, 2014)
Background and study aims: Hypertriglyceridemia can be a primary cause for acute pancreatitis or secondary to other factors prior to the increase of lipid levels, or both. The aim of our study was to assess the severity of acute pancreatitis with elevation in serum triglyceride levels and report the outcomes of our series. Patients and methods: One hundred twenty?six patients of acute pancreatitis were admitted within 72 hours of onset of symptoms, out of whom 26 patients were excluded during the course of study due to preexisting comorbidities. 100 patients in the study population were divided into group A having serum triglyceride levels ≥500 mg/dl (n = 30) and group B having <500 mg/dl (n = 70) at the time of admission. Results: The mean age of group A was similar to group B (50.2 ± 17.1 vs 49.26 ± 17.2 years; p = 0.860). Most common etiological factor of acute pancreatitis was found to be gall stones (56%) in both groups. Ranson's score at admission in group A was 2.93 ± 0.22 and in group B it was 1.34 ± 0.99. Mortality below two weeks was noted in (12/30, 40%) of group A and (6/70, 8%) of group B patients, which was statistically significant, (p = 0.015). Conclusions: The final conclusion of this study was that patients of acute pancreatitis with elevated triglyceride levels form a morbid group and these should be monitored aggressively for the development of any complications. DOI: http://dx.doi.org/10.3126/ajms.v5i4.9971 Asian Journal of Medical Sciences 2014 Vol.5(4); 21-24